2010
DOI: 10.1103/physrevb.82.195422
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of thermal conductivity in graphene nanoribbons with rough edges

Abstract: We analyze numerically the thermal conductivity of carbon nanoribbons with ideal and rough edges. We demonstrate that edge disorder can lead to a suppression of thermal conductivity by several orders of magnitude. This effect is associated with the edge-induced Anderson localization and suppression of the phonon transport, and it becomes more pronounced for longer nanoribbons and low temperatures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
149
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(165 citation statements)
references
References 32 publications
2
149
0
14
Order By: Relevance
“…24 Several ways to reduce the thermal conductivity have already been examined, such as interface mismatching between graphene and nanoribbons, 25,26 the presence of isotopes, [27][28][29][30] cross-plane phonon coupling in a few layers of graphene, 31 strain, 32 random hydrogen vacancies in graphene, 33 and point defects. [34][35][36] Edge disorder has been predicted theoretically to suppress heat conductance of graphene nanoribbons, [37][38][39] and ZT exceeding 3 has been theoretically predicted for such systems in the diffusive limit. 40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…24 Several ways to reduce the thermal conductivity have already been examined, such as interface mismatching between graphene and nanoribbons, 25,26 the presence of isotopes, [27][28][29][30] cross-plane phonon coupling in a few layers of graphene, 31 strain, 32 random hydrogen vacancies in graphene, 33 and point defects. [34][35][36] Edge disorder has been predicted theoretically to suppress heat conductance of graphene nanoribbons, [37][38][39] and ZT exceeding 3 has been theoretically predicted for such systems in the diffusive limit. 40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The major effect in limiting thermal conductivity in 1D channels, however, seems to be boundary scattering [24,61,9]. Two orders of magnitude reduction in thermal conductivity has been reported for several low-dimensional materials due to roughness compared to the pristine materials, which significantly improve their thermoelectric properties [61,62,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several works have shown that the transports properties of low-dimensional systems are significantly degraded by the introduction of scattering centers and localized states [9,10,22,14,23,24,25]. In the case of electronic transport, even a small degree of disorder can drastically reduce the electronic conductivity (especially in AGNRs rather than ZGNRs), even driving carriers into the localization regime and introduce 'effective' transmission bandgaps [15,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations